The absorber in self-excited system with random excitation - Anh, Nguyen Dong; Duc, Kieu The (Vietnam Journal of Mechanics, 1990)
In this paper, the absorber effect for self-excited system with random excitation is examined. It turns out that the random-self-oscillations can be suppressed by increasing the damping coefficient of the absorber. The results are obtained by averaging method and the FPK one.